2014
DOI: 10.1016/j.eats.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Re-Tensioning Technique to Cover the Graft With Remnant in Anterior Cruciate Ligament Reconstruction

Abstract: A number of remnant-preserving techniques to restore proprioceptive function in anterior cruciate ligament reconstruction have been described. However, they might not cover the significant amount of the graft with the synovium of the remnant in many cases. We introduce a simple technique that can cover nearly the entire graft with the synovium by re-tensioning the remnant, which might enhance synovialization of the graft and restoration of proprioception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…During the ACL reconstruction procedure, the tibial side ACL remnant would be impaired. As introduced by Ahn et al [1] and Noh et al [37] with medial traction of the remnant using sutures and with final hand reaming technique could reduce additional injury of remnant ACL tibia foot print. Seventh, the suture material used in repair was No.…”
Section: Discussionmentioning
confidence: 99%
“…During the ACL reconstruction procedure, the tibial side ACL remnant would be impaired. As introduced by Ahn et al [1] and Noh et al [37] with medial traction of the remnant using sutures and with final hand reaming technique could reduce additional injury of remnant ACL tibia foot print. Seventh, the suture material used in repair was No.…”
Section: Discussionmentioning
confidence: 99%
“…Merter used the Cybex apparatus to measure and compare the proprioception after allogeneic and autologous ACL reconstruction, and the results showed no difference in postoperative proprioception [19]. Noh covered the graft surface with the retained ACL stump, which finally improved the healing speed of the graft, increased its strength, and improved knee joint proprioception [20]. In this study, the angle reconstruction method revealed a significant difference at 3 months and 6 months but no difference was found at 12 months, which meant that in group A, the proprioception of ACL was better than in group B.…”
Section: Discussionmentioning
confidence: 99%
“…3,13 In addition, method modifications include positioning the graft as “behind the remnant” 23,24 and retensioning. 25,26 A previous study reported that the remnant tensioning is simple and preserves more remnant; 2 however, its method has not been developed for different femoral fixations, such as the use of an interference screw. Therefore, we modified the tensioning method to include direct suturing to the intra-articular part of the graft.…”
Section: Introductionmentioning
confidence: 99%